2021
DOI: 10.3390/molecules26185462
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the GPI Transamidase Complex by Screening for Amino Acid Mutations in Each Subunit

Abstract: Glycosylphosphatidylinositol (GPI) anchor modification is a posttranslational modification of proteins that has been conserved in eukaryotes. The biosynthesis and transfer of GPI to proteins are carried out in the endoplasmic reticulum. Attachment of GPI to proteins is mediated by the GPI-transamidase (GPI-TA) complex, which recognizes and cleaves the C-terminal GPI attachment signal of precursor proteins. Then, GPI is transferred to the newly exposed C-terminus of the proteins. GPI-TA consists of five subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previous efforts to measure GPI-T activity typically used cell lysates, crude microsomes, or cell-free translation systems and required analyses by SDS-PAGE and autoradiography or flow cytometry. 29,51,52 Two similar in vitro fluorescence assays have also been reported that require long incubation times (9 h to overnight) with a minimalistic peptide substrate, one using trypanosomal lysates or purified T. brucei Gpi8, 38 and the second using Candida albicans microsomes. 53 In both cases, the synthetic peptide substrates were Cterminally labeled with the fluorophore 7-amino-4-methylcoumarin and lacked the C-terminal signal sequence that is necessary for recognition by GPI-T. 5 A high-throughput assay using purified GPI-T and more native-like peptide substrates would be advantageous to probe the function of each individual subunit in a reliable, time-dependent manner.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous efforts to measure GPI-T activity typically used cell lysates, crude microsomes, or cell-free translation systems and required analyses by SDS-PAGE and autoradiography or flow cytometry. 29,51,52 Two similar in vitro fluorescence assays have also been reported that require long incubation times (9 h to overnight) with a minimalistic peptide substrate, one using trypanosomal lysates or purified T. brucei Gpi8, 38 and the second using Candida albicans microsomes. 53 In both cases, the synthetic peptide substrates were Cterminally labeled with the fluorophore 7-amino-4-methylcoumarin and lacked the C-terminal signal sequence that is necessary for recognition by GPI-T. 5 A high-throughput assay using purified GPI-T and more native-like peptide substrates would be advantageous to probe the function of each individual subunit in a reliable, time-dependent manner.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…A robust method to quantify the activity of purified GPI-T in a time-dependent manner has not been reported. Previous efforts to measure GPI-T activity typically used cell lysates, crude microsomes, or cell-free translation systems and required analyses by SDS-PAGE and autoradiography or flow cytometry. ,, Two similar in vitro fluorescence assays have also been reported that require long incubation times (9 h to overnight) with a minimalistic peptide substrate, one using trypanosomal lysates or purified T. brucei Gpi8, and the second using Candida albicans microsomes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GPI-APs are produced by coupling of the completed GPI anchor, prefabricated by stepwise transfer from activated precursors of the corresponding carbohydrate and EtN-P residues to PI at the luminal face of the ER membranes, to the carboxy-terminus of the polypeptide precursor moiety upon its translation and transient arrest at the ER membranes (for a review, see [25,26]). Total synthesis of the GPI anchor in mammalian cells requires 13 reactions catalyzed by more than 23 gene products, among them for transfer and amide coupling of the GPI anchor to the polypeptide moiety the membrane-bound GPI transamidase (GPI-T), including the catalytic subunits PIG-K and GPAA1 and the regulatory subunits PIG-S, PIG-T and PIG-U in mammals [27], including humans [28], and their homologues in Drosophila [29] and yeast (for instance GPI8 as PIG-K homolog) (for a review, see [30][31][32][33]). Consequently, the polypeptide precursor is equipped with two signals, a GPI attachment signal sequence at their carboxy-terminus recognized by the GPI-T [34][35][36] and a typical secretory pathway signal sequence at their amino-terminus for translocation into and quality control (and degradation) at the ER membranes [37][38][39][40] and subsequent transport to the PMs [41].…”
Section: Biogenesis and Expression At Pms Of Gpi-apsmentioning
confidence: 99%